Cellular microbiology: Bacterial toxin interference drives understanding of eukaryotic cell function. (17th March 2020) - Lemichez, Emmanuel; Popoff, Michel Robert; Satchell, Karla J. F.
Abstract: Intimate interactions between the armament of pathogens and their host dictate tissue and host susceptibility to infection also forging specific pathophysiological outcomes. Studying these interactions at the molecular level has provided an invaluable source of knowledge on cellular processes, as ambitioned by the Cellular Microbiology discipline when it emerged in early 90s. Bacterial toxins act on key cell regulators or membranes to produce major diseases and therefore constitute a remarkable toolbox for dissecting basic biological processes. Here, we review selected examples of recent studies on bacterial toxins illustrating how fruitful the discipline of cellular microbiology is in shaping our understanding of eukaryote processes. This ever‐renewing discipline unveils new virulence factor biochemical activities shared by eukaryotic enzymes and hidden rules of cell proteome homeostasis, a particularly promising field to interrogate the impact of proteostasis breaching in late onset human diseases. It is integrating new concepts from the physics of soft matter to capture biomechanical determinants forging cells and tissues architecture. The success of this discipline is also grounded by the development of therapeutic tools and new strategies to treat both infectious and noncommunicable human diseases.